Receptive music therapy to reduce stress and improve wellbeing in Italian clinical staff involved in COVID-19 pandemic: A preliminary study - Giordano, Filippo (Arts Psychother, 2020)
The influence of music therapy (MT) as a support intervention to reduce stress and improve wellbeing in Clinical Staff (CS) working with COVID-19 patients was evaluated. Participants were enrolled as a result of spontaneous agreement (n = 34) and were given remote receptive MT intervention over a 5-week period. Their levels of tiredness, sadness, fear and worry were measured with MTC-Q1 before and after MT intervention. An immediate significant variation in the CS emotional status was observed. The results seem to confirm that in an emergency situation, it is possible to put in place a remote MT support intervention for CS exposed to highly stressful situations.